Numerical Study of Thermoelectric Generation Within a Continuous Flow Porous Media Burner - Henriquez-Vargas, L; Donoso-Garcia, P (2013)
A numerical study based on direct thermal to electric energy conversion was performed in a continuous flow porous media burner. The optimal lengths and placements of thermoelectric elements for a set of operational variables (filtration velocity and composition of gas mixture) were sought in order to maximize the system overall efficiency. A twoerature resistance model for finite time thermodynamics was developed for the thermoelectric elements energy fluxes. Different operational variable sets that allowed wave stabilization inside the reactor were employed, giving rise to different thermal gradients and total power output. Results indicate an optimal thermoelements length and region for its placement inside the steep thermal gradients for maximum power production. © 2013 by Begell House, Inc.